2018
DOI: 10.3748/wjg.v24.i8.941
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of TPMT and NUDT15 polymorphisms in Chinese patients with inflammatory bowel disease

Abstract: AIMTo observe gene polymorphisms of TPMT and NUDT15, and compare their predictive value for azathioprine (AZA)-induced leukopenia in inflammatory bowel disease (IBD).METHODSThis study enrolled 219 patients diagnosed with IBD in Xiangya Hospital, Central South University, Changsha, China from February 2016 to November 2017. Peripheral blood of all patients was collected to detect their genotypes of TPMT and NUDT15 by pyrosequencing at the Department of Clinical Pharmacology, Hunan Key Laboratory of Pharmacogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 22 publications
4
37
0
Order By: Relevance
“…Detailed information of 19 studies evaluating the effect of concomitant treatment agents on the development of TIL can be found in Table S4 …”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Detailed information of 19 studies evaluating the effect of concomitant treatment agents on the development of TIL can be found in Table S4 …”
Section: Resultsmentioning
confidence: 91%
“…Six studies showed no effect of concomitant corticosteroid use on TIL development . One Chinese cohort study showed that patients receiving concomitant corticosteroids had a significant lower risk to develop TIL (OR 0.20 (95% CI 0.05‐0.80)) …”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations